Tarian Lego-lego sebagai Pendampingan Pastoral bagi Masyarakat Alor - Inger Gloria Manimoy (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2021)
Culture is often regarded as taboo and contrary to religious values. Whereas when viewed more in culture has values that if useful to learn. Lego-lego dance is one of the dances originating from Alor regency, East Nusa Tenggara. In addition to other traditional activities this dance also has the meaning of reconciliation that can restore a relationship that has been damaged. This dance indirectly becomes a medium of conflict resolution for every conflict in Alor society. In this paper, qualitative methods are used with data collection techniques, namely observations and interviews. If this writing can be seen as a method offered in conflict resolution in Alor society.